1978
DOI: 10.1172/jci109126
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Jejunum and Ileum in Rats

Abstract: A B S T R A C T During osmotic diarrhea, loss of water and electrolytes appears to be greater in infants than in adults. In 2-, 3-, and 7-wk-old rats, we studied net transport of H20, Na, and Cl, during in vivo perfusion of segments of the jejunum and ileum, from solutions with osmolalities of 300, 375, 500, or 700 mosmol/kg. In the jejunal segments, from the hypertonic solutions net transport of H20, Na, and Cl was into the lumen and greater in the 2-than 7-wk-old rats. In the ileal segments, transport of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Because net absorption and net secretion rates are the sum of the unidirectional fluxes, lumen-to-plasma and plasma-to-lumen, it is possible that an alteration in the magnitude of one or both of these fluxes were responsible for the observed developmental changes. The results of the present study are in agreement with those of our previous studies which showed that when the intestinal lumen was perfused with hypertonic solutions the permeability of the small intestinal mucosa to water decreased with increasing age (7).…”
Section: Discussionsupporting
confidence: 93%
“…Because net absorption and net secretion rates are the sum of the unidirectional fluxes, lumen-to-plasma and plasma-to-lumen, it is possible that an alteration in the magnitude of one or both of these fluxes were responsible for the observed developmental changes. The results of the present study are in agreement with those of our previous studies which showed that when the intestinal lumen was perfused with hypertonic solutions the permeability of the small intestinal mucosa to water decreased with increasing age (7).…”
Section: Discussionsupporting
confidence: 93%
“…At the intestinal level, previous studies have shown that the inhibitory effects of dopamine on jejunal sodium absorption and Na ϩ -K ϩ -ATPase activity in rat jejunal epithelial cells are limited to animals under 20 days of age, adult animals being insensitive to the inhibitory effects of dopamine (12,44,46). Intestinal function has a great impact during early postnatal life, not only on the uptake of nutrients but also on the maintenance of electrolytes and water metabolism (19,50). In fact, although nephrogenesis is completed at birth, renal tubular function continues to develop postnatally, and the kidney has a limited capacity to regulate fluids and electrolyte homeostasis (34).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal function is determined by a developmental process that has a great impact in maintaining electrolyte and water metabolism (Younoszai et al ., 1978). At this stage of maturation, the possible occurrence of complementary functions between the intestine and the kidney may be essential to achieve adequate electrolyte and water homeostasis.…”
Section: Discussionmentioning
confidence: 99%